Postabortion Family Planning and Associated Factors Among Women Attending Abortion Service in Dire Dawa Town Health Facilities, Eastern Ethiopia - Motuma, Venus Shewangizaw; Yadeta, Tesfaye Assebe; Alemu, Addisu; Yuya, Mohammed; Eshetu, Bajrond; Balis, Bikila; Bekana, Miressa; Merga, Bedasa Taye; Oljira, Lemessa (Frontiers in Reproductive Health, 2022)
Background Postabortion family planning is a part of comprehensive package of postabortion care. However, it did not receive due attention to break the cycle of repeated abortion, unintended pregnancies, and abortion-related maternal morbidity and mortality. Therefore, this study aimed to determine the utilization of postabortion family planning and associated factors among women attending abortion service in Dire Dawa health facilities, Eastern Ethiopia. Methods A facility-based cross-sectional study design was employed among 483 clients who sought abortion service in Dire Dawa from 15 May to 30 June 2020. A structured interviewer-administered questionnaire was used for data collection. The collected data were entered into EpiData version 3.2 and exported to SPSS version 22 for analysis. The multivariate logistic regression models were fitted to identify factors associated with utilization of postabortion family planning. Adjusted odds ratios (AORs) along with 95% CI were estimated to measure the strength of the association and statistical association was declared statistical at a p-value < 0.05. Results More than three-fourths (77.8%) [95% CI: (73.4–81.6%)] of respondents were utilized postabortion family planning methods. Respondents with age 15–24 years [AOR: 5.59, (95% CI: (1.5, 19.7)], attended postsecondary [AOR: 7.6, (95% CI: (2.7, 21.2)], single marital status [AOR: 11.1, (95% CI: (4.6, 26.5)], a monthly income 500–1,000 birr [AOR: 7.9, (95% CI: (3.2, 19.4)], parity ≥ 5 [AOR: 0.41, (95% CI: (0.18, 0.92)], desire of current pregnancy [AOR: 4.2, (95% CI: (1.9, 9.3)], and ever used family planning [AOR: 4.4, (95% CI: (2.2, 8.9)] were major factors significantly associated with postabortion family planning utilization. Conclusion In this study, more than three-fourths of respondents utilize postabortion family planning. Most of the factors associated with postabortion family planning were modifiable. Therefore, policymakers and health planners need to integrate with comprehensive abortion care to improve the utilization of postabortion family planning.